Renewable energy dynamics in Southeast Asia: Analyzing the impact of CO2 emissions, geopolitical risk, tourism, and GDP through FMOLS and CCR estimation approach - Hechmi, Soumaya (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the impact of CO₂ emissions, geopolitical risk, economic growth, and tourism on renewable energy consumption (as a proxy for clean energy) in five Southeast Asian countries from 1995 to 2023. The research aims to identify key drivers and barriers to clean energy adoption in the region. The study employs the Fully Modified Ordinary Least Squares (FMOLS) regression technique to analyze the long-term relationships between the variables. Additionally, Canonical Cointegrating Regression (CCR) estimation is used as a robustness check to validate the findings. The results reveal that CO₂ emissions negatively affect clean energy consumption in Indonesia, Malaysia, and the Philippines but improve renewable energy adoption in Thailand. Economic growth has a significant negative impact on clean energy in Indonesia, Thailand, and Vietnam, whereas it serves as a driver in Malaysia. Geopolitical risk exerts a strong adverse effect on renewable energy consumption only in the Philippines and Vietnam. Finally, tourism is negatively associated with clean energy solely in Malaysia. The results show that economic and geopolitical considerations have varying effects on the adoption of renewable energy throughout Southeast Asia, indicating that each country needs a different approach to policy. In support of clean energy adoption, policymakers must devise personalized strategies that cater to the distinct challenges of every country. In this regard, it could involve adopting carbon pricing in those countries with high-emitting characteristics, fostering stable geopolitics to hedge against risks to investments, and synchronizing tourist development with sustainable goals. Research also calls for regional coordination so that one may consolidate efforts with the possibility of aggregating resources by which Southeast Asian countries can navigate commonalities during a transition to renewable energy.